CHINA DJIBOUTI STRATEGIC PARTNERSHIP THROUGH BELT AND ROAD INITIATIVE: GEOSTRATEGIC VIEWPOINT - Rakhmadi, Roby; Ananda, Darra (Gapenas Publisher, 2024)
This article aims to explain the effect of increasing threats to strategic changes in China's foreign policy. In order to protect its interests abroad, the strategic partnership with Djibouti is an effort made by China on the African continent. The Strategic Partnership between the two countries is seen as a vehicle for foreign policy goals in the form of cooperation with an interdependence pattern. This study uses secondary data through literature study with official documents from the official websites of the Ministry of Foreign Affairs of the People's Republic of China and the Ministry of Foreign Affairs of the Republic of Djibouti as well as online data searches. The author uses qualitative research methods that refer to the concept of strategic partnership and the theory of interdependence. As a foreign policy instrument, strategic partnerships are able to support the demands of global dynamics and fulfill China's interests in the global sphere. This study finds that the strategic partnership with Djibouti is the first step in increasing the global integration of the African continent towards China